BUDAYA PENGGUNAAN ALAT BANTU PENERJEMAHAN (CAT TOOLS) DALAM PROSES MENERJEMAHKAN - Dian Wulandari (Asosiasi Dosen Muda Indonesia, 2023)
Translation is the transferring process of language from source language into target language with the translation results being made as natural as possible. The problems of the research are positive and negative implications for the work culture of translators and the social changes that occur in society because of using CAT Tools. The purpose of the research is to find out the positive and negative implications of CAT Tools on the work culture of translators as well as identify social changes that occur in society because of using CAT Tools. The method used in this research is qualitative descriptive method. The data collection techniques used were interviews and observation. The results obtained are that there are several positive and negative implications of using CAT Tools on work culture of translators, besides that, the using of CAT Tools creates changes in social values in society.